Ameliorating effects of metabolic syndrome with the consumption of rich-bioactive compounds fruits from Brazilian Cerrado: a narrative review - Santos, Daiane Costa dos; Oliveira Filho, Josemar Gonçalves de [UNESP]; Sousa, Tainara Leal de; Ribeiro, Carolina Barbosa; Egea, Mariana Buranelo (Taylor & Francis, 2021)
Evidence suggests that bioactive compounds present in fruits and vegetables, including carotenoids, polyphenols, and phytosterols, may have beneficial effects against the development of obesity and other diseases. The fruits of the Brazilian Cerrado are rich in biologically active compounds but are underexplored by the population being used only locally dietary consumption. The objective of this review is to direct attention to the bioactive compounds already elucidated for the fruits of “Cerrado” cashew (Anacadium othanianum Rizz.), baru almond (Dipteryx alata Vogel), cagaita (Eugenia dysenterica DC.), “Cerrado” pear (Eugenia klotzschiana Berg), mangaba (Hancornia speciosa), and pequi (Caryocar brasiliense Camb), demonstrating possible metabolic effects of the consumption of these fruits on the metabolic syndrome and its risk factors. Studies have shown that Cerrado native fruits have a high content of bioactive compounds such as phenolic compounds, which also demonstrate high antioxidant capacity and may be related to the protective effect in metabolic syndrome-related diseases by act as inhibitors in various processes in lipid metabolism and glucose transport. Although more scientific evidence is still needed, the consumption of native fruits from the Cerrado seems to be a promising strategy which —along with other strategies such as nutritional therapy— can ameliorate the effects of the metabolic syndrome.
Keywords: Brazilian native fruits; diabetes; dyslipidemia; functional foods; obesity